Paradoxical rise in blood pressure during ultrafiltration is caused by increased cardiac output - Günal, AI; Karaca, I; Çeliker, H; Ilkay, E; Duman, S (Wichtig Editore, 2002)
Background: In some haemodialysis patients, blood pressure increases during the dialysis session despite ultrafiltration (UF). Methods: We investigated six such patients who were not responsive to hypotensive drugs. Their echocardiograms were obtained prior to and during the dialysis session. Results: After the mean 2520 +/- 1698 (4.5 +/- 2.3% of BW) nil of fluid was removed, the cardiac systolic function parameters significantly improved and maximum mean arterial pressure rose (from 107 +/- 5 to 118 +/- 6 mmHg, p<0.027). This increase in blood pressure was accompanied by an increase in cardiac index (from 3.8 +/- 0.6 to 4.8 +/- 1.1 L/min/m(2), p<0.027). With continuing UF, after a mean fluid removal of 4133 +/- 1622 (7.5 +/- 2. 1 % of BW) ml, normal blood pressure was achieved in all patients. Previously increased ejection fraction and fractional shortening decreased. End-diastolic volume significantly decreased from 98 +/- 34 to 78 +/- 35 ml/m(2) indicating normovolemia. This decrease in blood pressure was accompanied by a return of cardiac index to normal values (from 4.8 +/- 1.1 to 3.1 +/- 0.8 L/min/m(2), p<0.027). There was a positive correlation between mean arterial pressure and cardiac index (r = 0.56, p = 0.017). Conclusion: We hypothesize that our patients had passed the top of the Frank-Starling curve and were on the descending limb at the initial examination. With UF, patients first shifted to the left and upward on the curve. With further UF, they came down the ascending limb of the curve. In conclusion, paradoxical blood pressure rise during UF is caused by increased cardiac output, mediated by volume overload and can be treated by intensified UF.
Keywords: haemodialysis; ultrafiltration; hypertension; cardiac index; echocardiography